An examination of speechreading and spelling accuracy with high school students who are deaf or hard of hearing. (3rd April 2017) - McCarthy, Jillian H.; Schwarz, Ilsa; Cannon, Lindsay
Abstract : Numerous studies have demonstrated that spelling presents unique challenges for children who are deaf or hard of hearing (d/hh) and most do not develop age appropriate spelling skills. For these children, information about the sound structure of a word is reduced due to limited auditory input. However, children who are d/hh do have access to visual information about the sounds in words through speechreading. The objective of this study was to explore the degree to which speechreading cues are used to support spelling during a single word spelling test. Fourteen high school students who are d/hh from a state school for the Deaf, participated in two spelling conditions; Condition A in which visual information from speechreading was available and Condition B in which it was not. Spelling errors were coded by Condition for overall accuracy and accuracy based upon the visibility of the initial sound and the ambiguity of the American Sign Language (ASL) sign or picture. A multi-linguistic coding system was also used to assess each child's understanding of the phonological, morphological, orthographic, semantic, and visual imagery rules that apply to written words. Results show that total scores in both Conditions were low although spelling accuracy for the words with ambiguous signs and pictures improved when visual information from speechreading was available. The visibility of the initial speech sound did not affect test scores. The multi-linguistic analysis showed that the participants produced more semantic, morphological, and phonological errors than other errors types. The results from this study suggest that, at least with this group of participants, there is a need for greater emphasis on teaching the linguistic foundations that guide spelling, coupled with an emphasis on using the visual speech signal to obtain linguistic information.